(untitled) (Research, Society and Development, 2020)
The study aimed to understand the perception of university students with physical disabilities (PD) about school inclusion. Four students PD, wheelchair users who attended higher education courses at a public university participated in the research. The survey was conducted through the interview and form. In the treatment of data, content analysis was used, being structured in three categories: affective relationships (between teacher / student with DF, and non-disabled student / student with PD); school activities and teaching practice; and physical access difficulties. In the results, the participants showed positive affection in the teacher-student relationship; except one participant who indicated a higher prevalence of negative relationships with teachers; in the relationship between disabled and non-disabled students, there was a greater report of the frequency of negative interactions. Regarding school activities and teaching practice, the participants had difficulties in fine motor skills; three of them mentioned that there was in the teaching practice, flexibility / differentiation in the methodology and in the evaluation; one participant reported the teachers’ little didactic and evaluative diversification. In the category physical access difficulties, for the participants, accessibility was mostly non-existent and / or precarious. We conclude that it is necessary to reflect on inclusive educational policy and practices in schools, work to raise awareness of the rights of people with disabilities and the possibilities of successful inclusive practices for students with PD in basic education, with a view to successful learning, social participation and empowerment.